Whole-body and site-specific bone remodelling in patients with previous femoral fractures: relationships between reduced physical activity, reduced bone mass and increased bone resorption. - Wand, J; Smith, T; Green, JR; Hesp, R; Bradbeer, J; Reeve, J (1992)
1. A new tracer method is described for the non-invasive measurement of bone formation in the proximal femur. The method is based on our previously described whole-body method using 85Sr as the tracer (Reeve, J., Hesp, R. and Wootton, R. Calcif. Tissue Res. 1976; 22, 191-206). It allows correction to be made for long-term exchange processes within the skeleton. 2. The method has been applied in a study of regional and whole-body bone formation in 12 rehabilitated patients who had previously suffered a fracture of the proximal femur. Twelve healthy control subjects were studied, who were selected for their good health and continued physical activity. The aim was to explore the relationship between bone formation and physical activity. 3. Bone formation was similar in the two groups, both regionally and in the whole body. Based on analyses of four cadaver specimens, bone formation in the proximal femur was about one and two-thirds times that in the whole skeleton when related to mass of calcium in the region of interest. 4. Whole-body bone resorption, estimated from five measurements per subject of hydroxyproline excretion in relation to creatinine excretion, was significantly higher in the fracture patients (P < 0.01, Wilcoxon's test). 5. Estimates of current physical activity (and immediate pre-fracture physical activity) were made with a newly devised questionnaire. Historical levels of physical activity (at ages 15-45 years) were determined with Astrom's questionnaire. No bone formation index correlated with any index of physical activity. Urinary hydroxyproline excretion correlated inversely both with current physical activity and historical physical activity (for both regression coefficients P < 0.01). 6. The results are discussed in the light of our current understanding of the control of bone remodelling by the discrete basic multicellular units of bone. The opportunity to study regional bone resorption by the additional use of serial dual X-ray absorptiometry of the same region will in future allow the direct monitoring of the effects of therapeutic interventions which have been designed to prevent contralateral hip fracture.